Preparation and Studies on Carbon Nanotubes and Zinc Encorporated Carbon Nanotubes - Jaya Vinse Ruban, Y. (Asian Journal of Chemistry, 2010)
This study is concerned about the one step water assisted synthesis of high quality carbon nanotubes directly from graphite and the carbon nanotube was encorporated with zinc metal. FTIR technique provide the information about the formation of carbon nanotubes and zinc encorporated carbon nanotubes. XRD analysis was carried out to find out the diameter of the encorporated carbon nanotubes.